2016
DOI: 10.1097/shk.0000000000000499
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Endothelial Growth Factor, Angiopoietin-2, Reduces Indices of Ards and Mortality in Mice Resulting from the Dual-Insults of Hemorrhagic Shock and Sepsis

Abstract: We have demonstrated hemorrhagic shock “priming” for the development of indirect (i)ARDS in mice following subsequent septic challenge and show pathology characteristic of patients with iARDS, including increased lung micro-vascular permeability and arterial PO2/FI02 reduced to levels comparable to mild/moderate ARDS during the 48 hours following hemorrhage. Loss of endothelial cell (EC) barrier function is a major component in the development of iARDS. EC growth factors, Angiopoietin (Ang)-1 & 2, maintain vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
(65 reference statements)
0
27
0
Order By: Relevance
“…A mouse model of hemorrhagic shock induced “priming” followed by the induction of sepsis for the development of iARDS [a model with which we have considerable experience and in which we have shown induces arterial PO 2 /FIO 2 , (mmHg) of ~150 mmHg by 24 h post-shock/sepsis along with evidence of protein leak and morphological changes (19)] was used here (15, 16, 20). Mortality associated with this model is typically 60–70% after 48 h post-sepsis (15, 20).…”
Section: Methodsmentioning
confidence: 99%
“…A mouse model of hemorrhagic shock induced “priming” followed by the induction of sepsis for the development of iARDS [a model with which we have considerable experience and in which we have shown induces arterial PO 2 /FIO 2 , (mmHg) of ~150 mmHg by 24 h post-shock/sepsis along with evidence of protein leak and morphological changes (19)] was used here (15, 16, 20). Mortality associated with this model is typically 60–70% after 48 h post-sepsis (15, 20).…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Notably, effects of endothelial receptors and changes in Ang-2 levels have been involved in the underlying mechanisms contributing to the link between circulating Ang-2 and the risk of mortality in patients with ARDS. 11,12 Indeed, an early prospective cohort study showed that increased plasma Ang-2 levels independently predicts mortality in over 900 patients with acute lung injury (ALI) or ARDS. 13 Subsequent studies showed that selective temporal blockade of Ang-2 function greatly improved PaO 2 /FiO 2 , decreased lung protein leak and indices of inflammation, and finally improved overall survival in murine models of ARDS.…”
Section: Introductionmentioning
confidence: 99%
“…Among wildtype mice after Hem-CLP, the P:F ratio (arterial P02:Fi02) decreases, suggesting loss of pulmonary compliance (99, 120). Among mice who were either PD-1 −/− or PD-L1 −/− , indices of lung inflammation (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…decreases, suggesting loss of pulmonary compliance. 99,118 Among mice who were either PD-1 −/− or PD-L1 −/− , indices of lung inflammation (e.g., IL-6, MIP-2, myeloperoxidase) and injury (pulmonary edema, protein leak) were mitigated following the same Hem-CLP challenge. 99,119 Histologic analysis has also revealed increased leukocyte presence and cellular A o in lung tissue following Hem-CLP, a finding attenuated by PD-1 gene deletion.…”
Section: End-organ Injury -The Lungmentioning
confidence: 99%